2018
DOI: 10.1007/s00787-018-1143-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the ADOS and ADOS-2 in clinical practice

Abstract: The Autism Diagnostic Observation Schedule is a semi-structured, standardized assessment tool for individuals with suspected autism spectrum disorders (ASD) and is deemed to be part of the gold standard for diagnostic evaluation. Good diagnostic accuracy and interpersonal objectivity have been demonstrated for the ADOS in research setting. The question arises whether this is also true for daily clinical practice and whether diagnostic accuracy depends on specialized experience in the diagnostic evaluation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 62 publications
0
73
0
1
Order By: Relevance
“…In support of this interpretation, 1 study found that children in Sweden aged 7 to 12 years who received a diagnosis of autism in 2014 had a 50% lower autism symptom score than did those diagnosed in 2004, whereas the prevalence of autism simultaneously increased 5-fold in this age group. 9 In parallel, the pool of individuals with autism diagnoses from which participants in research experiments are extracted generally satisfy Autism Diagnostic Interview and Autism Diagnostic Observation Schedule criteria, a set of criteria for which there can be problems with reliability 10 , 42 and specificity. 43 , 44 Regardless of the cause, the hypothesis of a broadening understanding of autism is consistent with the marked increase in the prevalence of autism that has been observed in recent decades and attributed, among other possibilities, to less stringent case ascertainment.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this interpretation, 1 study found that children in Sweden aged 7 to 12 years who received a diagnosis of autism in 2014 had a 50% lower autism symptom score than did those diagnosed in 2004, whereas the prevalence of autism simultaneously increased 5-fold in this age group. 9 In parallel, the pool of individuals with autism diagnoses from which participants in research experiments are extracted generally satisfy Autism Diagnostic Interview and Autism Diagnostic Observation Schedule criteria, a set of criteria for which there can be problems with reliability 10 , 42 and specificity. 43 , 44 Regardless of the cause, the hypothesis of a broadening understanding of autism is consistent with the marked increase in the prevalence of autism that has been observed in recent decades and attributed, among other possibilities, to less stringent case ascertainment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Bieleninik and colleagues 98 published a multicentre trial of improvisational music therapy for children aged 4–7 years and found no reductions in ASD symptoms on the ADOS Social Affect domain after 5 months of therapy, compared to standard care. The authors suggest that this could be due to variability across therapists, clinical assessors 99 and the choice of ADOS as outcome measure, particularly because no previous well-controlled and blinded intervention studies 3 have found treatment effects on the ADOS. While this trial demonstrates the global feasibility of implementing music therapy in large-scale international settings, it also indicates the importance of choosing appropriate outcome measures for psychosocial interventions in heterogeneous neurodevelopmental populations.…”
Section: Discussionmentioning
confidence: 99%
“…Obregia" Clinical Psychiatry Hospital. A certified child and adolescent psychiatrist established the diagnosis of ASD, based on clinical evaluation and diagnostic tests, among which ADOS (Autism Diagnostic Observation Schedule) (30).…”
Section: Subjects and Sample Collectionmentioning
confidence: 99%